2018
DOI: 10.1029/2017jd027771
|View full text |Cite
|
Sign up to set email alerts
|

A Terrestrial Gamma‐Ray Flash inside the Eyewall of Hurricane Patricia

Abstract: On 23 October 2015 at ~1732 UTC, the Airborne Detector for Energetic Lightning Emissions (ADELE) flew through the eyewall of Hurricane Patricia aboard National Oceanic and Atmospheric Administration's Hurricane Hunter WP‐3D Orion, observing the first terrestrial gamma‐ray flash (TGF) ever seen in that context, and the first ever viewed from behind the forward direction of the main TGF gamma‐ray burst. ADELE measured 184 counts of ionizing radiation within 150 μs, coincident with the detection of a nearby light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Based on the RREA theory, the gamma rays produced by reverse positron beam have a harder spectrum (Bowers et al, 2018; Ortberg et al, 2020). In this case, the CG‐TGF produced 8 high‐energy BGO counts and 10 low‐energy NaI counts.…”
Section: Measurements and Analysismentioning
confidence: 99%
“…Based on the RREA theory, the gamma rays produced by reverse positron beam have a harder spectrum (Bowers et al, 2018; Ortberg et al, 2020). In this case, the CG‐TGF produced 8 high‐energy BGO counts and 10 low‐energy NaI counts.…”
Section: Measurements and Analysismentioning
confidence: 99%
“…Different authors have used different standards to define the luminosity of a TGF; the values for the lower limits on TGF luminosity in the right‐hand columns of Table 2 can be converted as follows. To convert to photons >1 MeV (as used by Bowers et al, 2018), divide the number of photons >20 keV by a factor of 5.41. This is a characteristic of the generic RREA spectrum (Dwyer, 2003; Dwyer & Smith, 2005).…”
Section: “Paralyzing” Tgfs and Compton Tail Analysismentioning
confidence: 99%
“…The idea that a TGF could have a reverse beam due to positron bremsstrahlung has been known to be possible in theory given the simulations presented in Dwyer (), though the feasibility of detecting such a reverse beam has not been explored in detail. Recently Bowers et al () believe they observed this phenomenon in the eyewall of Hurricane Patricia in the 2015 season. A TGF was detected onboard an aircraft at 2.6 km altitude, but the radio signal for the associated lightning strike suggested an upward motion of electrons (and therefore upward‐directed TGF).…”
Section: Background and Summarymentioning
confidence: 92%